Successful treatment of chronic venous leg ulcers with lyophilized cultured epidermal allografts - Slonková, Veronika (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2004)
The case of a 67-year-old woman with chronic venous leg ulcers and severe gonarthrosis is described. In spite of intensive therapy, the leg ulcers had persisted for 4 years and made the intended orthopaedic operation of the rightknee impossible. The patient was treated with lyophilized cultured epidermal allografts and her leg ulcers healed within 40 days. Lyophilized cultured epidermal allografts represent a modern type of active wound dressingthat leads to rapid healing of chronic venous leg ulcers and enables patients to undergo surgical intervention.
Keywords: Aged; Celične kulture; celjenje ran; Cells, Cultured; Freeze Drying; Koža umetna; Leg Ulcer; Liofilizacija; noga; Noga, ulkus; Rana, celjenje; rane; Skin, Artificial; Starostniki; Therapy; ulkus; Wound Healing; zdravljenje